2012
DOI: 10.1016/j.hkjn.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peritoneal dialysis on antioxidant defense system and oxidative stress

Abstract: Objective: In this study we investigated the effect of peritoneal dialysis (PD) on some antioxidant markers and lipid peroxidation. Methods: The levels of malondialdehyde (MDA), erythrocyte superoxide dismutase (SOD), glutathione peroxidase (GPx), vitamins A, E, and C, and total antioxidant capacity (TAC) were determined in 23 chronic ambulatory PD patients and 34 healthy controls. Results:The results showed MDA level in patients were not significantly different from those in controls. Erythrocyte SOD and GPX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Higher levels of MDA have been reported in patients with ESRD, HD, PD vs. HC (45, 46). There are also reports where no differences in MDA levels in patients with PD and HC (47). In our study, we found increased levels of LPO in all types of PT (48) and no correlation with the value of PET.…”
Section: Discussionmentioning
confidence: 98%
“…Higher levels of MDA have been reported in patients with ESRD, HD, PD vs. HC (45, 46). There are also reports where no differences in MDA levels in patients with PD and HC (47). In our study, we found increased levels of LPO in all types of PT (48) and no correlation with the value of PET.…”
Section: Discussionmentioning
confidence: 98%
“…It is of importance to note that our findings are in accordance with the report by Montazerifar et al . [17] The authors showed that decreased activity of enzymatic antioxidant defense system played a leading role in accelerated atherogenesis in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic kidney disease (CKD), structural damage and kidney dysfunction occur, this can trigger the emergence of oxidative stress caused by increased oxidant activity and decreased antioxidant systems which will later have an impact on the TAC (Putri & Thaha, 2014). A Journal homepage: https://e-journal.unair.ac.id/MBIO/ number of studies have reported TAC levels of CKD patients who undergo hemodialysis (HD) and nonhemodialysis (non-HD) that are quite varied and controversial (Mayer et al, 2003;Montazerifar et al, 2012). In addition, in Indonesia, especially in Surabaya, there is still no data on TAC CKD patients who undergo HD and non-HD.…”
Section: Introductionmentioning
confidence: 99%